Previous Prison Experience and Evaluation of the Quality of Prison Life - Stevanović, Ivana; Ilijić, Ljeposava; Vujičić, Nikola (NBP. Nauka, bezbednosti, policija, 2024)
In the paper, the authors analyse the relationship between the prison social climate and recidivism, that is, they connect the data obtained by measuring the quality of prison life (MQPL) with the dimension of previous prison experience. The paper examines the hypothesis that on some/certain aspects there will be differences in the perception of the prison social climate depending on whether the respondents are in prison for the first time, or they have already had prison experience. The main goal of the paper is to examine whether there are differences between persons who have previously served a prison sentence and those who have not, with regards to the perception of the quality of prison life. The research was carried out in the course of 2022, on a sample of 578 convicted adults, who are serving a prison sentence in Sremska Mitrovica Prison, Požarevac - Zabela Prison, Niš Prison, Belgrade Prison and Požarevac Prison for Women. Descriptive statistics and t-test were used in the paper. The most important results show that there are significant differences regarding the assessment of the quality of prison life in the following categories: Harmony Dimensions, Professionalism Dimensions and Wellbeing and Development Dimensions, and that each of those three categories is statistically significantly better rated by those who are not penological returnees. When it comes to the general assessment of the quality of prison life, the results showed that there are no significant differences between persons who have previously served a prison sentence and those who have not.